Proficiency in English for Describing Hotel Room Services: A Study of Ogan Hilir Hotel Employees - Taslim, M (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aims to analyze the ability of hotel employees in Ogan Ilir, South Sumatra, in explaining guest room facilities using English. English is an important skill for hotel employees to improve communication with foreign guests, especially in the area's growing hospitality sector. The research method used is a qualitative approach with data collection through interviews, observations and documentation. The participants of this study were 15 employees from several hotels in Ogan Ilir. This study measures their ability to use terms related to hotel facilities, such as room types, equipment, and available services. The results of the study show that the majority of employees have basic skills in using English, but there are still difficulties in explaining room facilities in detail and professionally. Some of the factors that affect these abilities are the lack of language training, formal education level, and work experience in the hospitality industry. This study recommends the existence of a special needs-based English training program in the hospitality sector to improve employee communication skills. This finding is also expected to be a consideration for hotel management in improving service quality through the development of human resources who are more skilled in English.